EFEKTIVITAS MEDIA SENI SIPA DALAM PENYAJIAN SENI BUDAYA DI BENTENG VESTENBURG SOLO TAHUN 2014 - Dewi, Tri Palupi (Transformasi, 2015)
Communication used by Solo International Performing Art to support effectivity themedia in presentation of cultural by using cultural communication to register and pull thecommunity into an entertainment as a Communication message in a SIPA Art Message. Thesuccess used of SIPA in supporting effectivity the presentation of cultural media is sign systemfor the performances, the artistic place to invite enthusiastic of audiences. Besides SIPA alsoworked with mass media to expanding network information, in attracting people toparticipations into sipa according show that inferred said staging sipa done in 2014 at thefort Vastenburg expressed effective and able to attract enthusiasthic of audiences around10000 peoples a day from 15000 tickets deployed, through the sign system, mass media, artsand culture, and performing arts.Key Words: Effectiveness, Art, Culture